PENINGKATAN KEMAMPUAN MENULIS PUISI SISWA DENGAN TEKNIK PEMODELAN - Ratnawati, Eny (Universitas Tanjungpura, 2021)
AbstractOne of the problems in the world of education today is the low quality of education caused by several factors including the low quality of learning caused by the ability of teachers who are still lacking, not using methods that are in accordance with the material being taught, an evaluation system that is not appropriate, and the ability of teachers. in learning activities is still lacking because the learning strategies carried out by teachers are still monotonous. Modeling technique is a learning concept that can help teachers improve students' writing skills so that they can be applied in their lives as family and community members. The purpose of this Classroom Action Research (CAR) is to determine the extent to which learning through modeling techniques improves the poetry writing skills of class VIII B students at SMP Negeri 5 Sungai Raya. In this Classroom Action Research (CAR) carried out in 2 cycles, from the results of the actions taken, the modeling technique is proven to be able to improve students' poetry writing skills in Indonesian lessons by reaching the KKM standard of 70. From 64.46% in cycle I, it can increase to 78.75% in cycle 2. The results of this action research show that learning Indonesian through modeling techniques is effective and can improve the poetry writing skills of class VIII B students at SMP Negeri 5 Sungai Raya.Â Â Keywords: Modeling Techniques, Writing Poetry